Mild and Versatile Potassium Fluoride/Tetrabutylammonium Fluoride Protocol for Ester Hydrolysis - Vijayalakshmi, D.; Balakrishna, K.; Mustafa, Shaik (Asian Journal of Chemistry, 2017)
A mild and versatile protocol of potassium fluoride/tetrabutylammonium fluoride (KF/TBAF) in aqueous tetrahydrofuran for ester hydrolysis has been developed. The method is applied on variety of aliphatic and aromatic ester moieties bearing acid or base sensitive functional groups. The conditions have been also applied on acetates to yield alcohols. The chirality of optically pure esters remained intact with the conditions of the reaction.